A method for preparing a back contact solar cell with tunneling oxide passivation contact
By cleaning with alkali liquid containing potassium hydroxide and polishing additives during the preparation of solar cells, the problem of inconsistent material reaction speed in the alkali washing process is solved, and the precise removal of winding plating and the improvement of battery efficiency is achieved.
Patent Information
- Application Number
- CN202411836837.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
When preparing back contact solar cells with tunneled oxidation passivation contact, the reaction speed of the material in the alkali washing process is inconsistent, resulting in incomplete cleaning or damage to the non-wound plating zone, affecting the battery efficiency and appearance quality.
Cleaning is carried out using alkali liquid containing potassium hydroxide and polishing additives. By adjusting the component ratio, cleaning temperature and time of the alkali liquid, the reaction rate is accurately controlled to ensure that the winding plating is removed without affecting the non-wounding plating area.
It realizes accurate removal of the front plating of solar cells, improves the conversion efficiency and stability of the battery, and is suitable for the stability and consistency requirements of mass production.
Smart Images

Figure CN119317233B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a method for preparing a back-contact solar cell with tunneling oxidation passivation contact. Background Art
[0002] TBC (Tunnel Oxide Passivated Contact Back Contact) cell technology is an emerging solar cell structure that combines the passivated contact technology of TOPCon (Tunnel Oxide Passivated Contact) cells with the back contact structure of IBC (Interdigitated back contact) cells. This type of cell not only has the advantages of high conversion efficiency and low attenuation performance of TOPCon cells, but also inherits the structural advantages of IBC cells, which can effectively reduce photocurrent loss, improve short-circuit current and fill factor, thereby achieving higher conversion efficiency.
[0003] However, in the process of preparing TBC cells, especially when performing two cleanings to remove poly wrapping, there are many technical challenges. Traditionally, due to the presence of the tunneling oxide layer, the cleaning process mainly relies on pickling, and commonly used chemicals include nitric acid and sulfuric acid. These pickling methods can effectively remove poly silicon and tunneling oxide layers, ensure the thoroughness of cleaning, and maintain consistency in appearance (small difference in reflectivity). However, the pickling process is accompanied by significant environmental pollution risks, especially nitric acid may release nitrogen oxides (such as NO, NO2) during preparation and use. These are atmospheric pollutants that can cause environmental problems such as photochemical smog. In addition, a large amount of waste gas and wastewater are also generated during the production and use of sulfuric acid, which contains harmful gases such as sulfur dioxide, causing air pollution and may form environmental problems such as acid rain.
[0004] In order to cope with the environmental impact, technicians began to consider the alkaline washing process. Although alkaline washing has certain advantages in environmental protection, it reacts quickly with poly silicon and silicon substrate, but reacts slowly with the tunnel oxide layer (SiOx), almost not at all. In this way, after the poly expansion area prepared by PECVD or LPCVD reacts with alkali to the tunnel oxide layer (SiOx), the reaction speed is greatly reduced. After alkaline washing, a certain reflectivity difference will be formed, which is reflected in the poor appearance of the battery.
[0005] Therefore, the technical team hopes to re-explore the alkaline washing process while maintaining the quality of the battery, so as to achieve precise removal of wrap-around plating and improve conversion efficiency.
[0006] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a back-contact solar cell with a tunneling oxidation passivation contact, so as to solve the problem of inconsistent reaction speeds of alkaline washing with different materials, thereby accurately controlling the reaction rate of each material, and ultimately achieving the purpose of accurately removing the wrap-around plating and improving the conversion efficiency.
[0008] The disadvantages of removing the plating by alkali washing at present are: long-term alkali washing to remove the plating will destroy the velvet surface of the non-plating area, resulting in different reflectivities on the same side; short-term alkali washing will result in incomplete removal of the plating on the four edges; that is, improper cleaning will result in over-polishing or unclean cleaning, obvious color difference after coating, poor passivation effect, and poor absorption of light, resulting in a reduction in the filling factor, and ultimately causing a reduction in efficiency. Therefore, the difficulty of the present invention is: how to use an alkali washing solution to remove the plating on the front side, while removing it cleanly, the velvet / polished surface of the non-plating area on the front side is not affected, avoiding different reflectivities and crystal sizes.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A method for preparing a back contact solar cell with a tunneling oxide passivation contact, comprising:
[0011] N-type silicon wafer is used as substrate, and the back contact structure uses single boron diffusion or P-poly as P-type doping area and N-poly as N-type doping area;
[0012] Among them, the wrap-around plating caused by P-poly or N-poly doping on the front side is removed by alkaline cleaning;
[0013] The alkali solution is prepared by mixing potassium hydroxide with a polishing additive, wherein the polishing additive includes a silane coupling agent, alkyl trimethyl ammonium bromide, a surfactant, polyethylene oxide and deionized water;
[0014] Silane coupling agent can be adsorbed on the surface of borosilicate glass and phosphosilicate glass grown on silicon wafers, protecting the two silicon oxide films from alkali corrosion during the de-plating process; alkyltrimethylammonium bromide can increase the corrosion rate of the de-plating in alkaline solution, making the de-plating removal faster and more thorough; surfactants can enhance the wetting and leveling effects of the polishing liquid; polyethylene oxide can enhance the stability and effect of additives; deionized water, as a solvent, provides the necessary liquid environment so that other components can be evenly distributed and function.
[0015] The dosage of each component in the alkali solution, the cleaning temperature and the cleaning time are matched according to the thickness of the poly. The present invention conducts multiple experiments with different liquid ratios, different reaction temperatures and different reaction times to establish a model for the dosage of each component in the alkali solution, the cleaning temperature and the cleaning time, and the thickness of the poly; in actual production, for a specific poly thickness, the optimal liquid ratio and reaction temperature are found through model fitting, and the cleaning time is adjusted based on the actual dissolution rate, ultimately achieving the purpose of accurately removing the wrap-around plating and improving the conversion efficiency.
[0016] Preferably, the dosage of each component in the alkali solution, the cleaning temperature and the cleaning time are matched according to the thickness of the poly, including:
[0017] Establish models for the dosage of each component in the lye solution, cleaning temperature and cleaning time, and poly thickness;
[0018] Based on the established model, the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time are calculated in real time for the poly thickness actually measured in each preparation;
[0019] Based on the optimal dosing ratio of alkali solution in actual production, the cleaning efficiency is evaluated by the change of poly thickness with cleaning time;
[0020] Based on the cleaning efficiency feedback, the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing of the non-wrap-around area under the current alkali solution formula are calculated and compared with the cleaning time predicted by the model;
[0021] Sort the minimum cleaning time, the maximum cleaning time and the model-predicted cleaning time in ascending order, and select the middle value after sorting as the adjusted cleaning time;
[0022] The adjusted cleaning time, the calculated optimal dosage and ratio of alkali solution, and the cleaning temperature are used as process parameters for cleaning and removal of poly.
[0023] Preferably, the change of poly thickness is detected by implementing a data acquisition system, and the acquisition frequency of the system is once per second.
[0024] Preferably, the establishment of the model comprises the following steps:
[0025] Set the parameter ranges for poly thickness, dosage of each component in the alkali solution, cleaning temperature and cleaning time;
[0026] Conduct multiple sets of experiments to record the effect of parameter changes on cleaning results at different poly thicknesses, and collect current density, efficiency, and surface quality data;
[0027] Analyze experimental data using statistical analysis software to identify the best parameter combinations as the basis for the model;
[0028] During each production process, the poly thickness value measured in real time is used as input into the model;
[0029] According to the current poly thickness value, the model calculates the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time in real time to control the execution of the cleaning process.
[0030] Preferably, the parameter range is set as:
[0031] The poly thickness is 40~200nm, the alkali solution includes potassium hydroxide and a polishing additive mixed in a mass ratio of 2~6:1, the polishing additive includes 0.1~0.5% silane coupling agent, 0.8~2.3% alkyltrimethylammonium bromide, 7~13% surfactant, 0.01~0.15% polyethylene oxide and the remainder deionized water; the cleaning temperature is 60~70℃; the cleaning time is 10~180sec.
[0032] Furthermore, when an N-type silicon wafer is used as a substrate, a back contact structure uses a single boron diffusion as a P-type doping region, and N-poly is used as an N-type doping region, the preparation process of the battery structure includes:
[0033] (1) Double-sided polishing of N-type silicon wafers: First polish in a slot machine, with a polishing thickness of about 5~10μm;
[0034] (2) Back side boron diffusion - Boron doping is performed in a high temperature furnace tube, and the doping promotion and oxidation are performed at a temperature of 850~1100℃. The BSG thickness is controlled at 90~150nm, and the doping square resistance is controlled at 350±100ohm / sq.
[0035] (3) Back laser patterning 1 to remove BSG in the N region - using a green laser with a power of 10W in a single scan to remove BSG in the back N region;
[0036] (4) Pickling to remove BSG on the front and edges - Use a chain cleaning machine with an HF concentration of 30% to 50% by volume to remove the BSG layer on the front and sides;
[0037] (5) Perform alkaline polishing on the back laser patterning 1 area, front side and edge - polishing using a tank cleaning machine, using potassium hydroxide: polishing additive = 2~5:1, temperature controlled at 80°C, polishing weight loss of about 0.15g;
[0038] (6) Back-side doping with N +-poly——Both PECVD and LPCVD methods can be used for doping; the thickness of doped poly is controlled at 50~140nm, the thickness of PSG is controlled at 30~60nm, and the doped square resistance is controlled at 30~60ohm / sq;
[0039] (7) Back laser patterning 2 to remove PSG in the P region - using a green laser with a power of 10W in a single scan to remove PSG in the back P region;
[0040] (8) Back laser patterning 3 to remove the oxide layer BSG / PSG at the PN gap - using a green laser with a power of 15W for a single scan to remove the oxide layer BSG / PSG at the back PN gap;
[0041] (9) Pickling to remove PSG on the front and edges - Use a chain cleaning machine with an HF concentration of 10% to 30% by volume to remove the PSG layer on the front and sides;
[0042] (10) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer: the alkali solution is prepared by mixing potassium hydroxide and polishing additives in a mass ratio of 2-6:1, the polishing additives include 0.1-0.5% silane coupling agent, 0.8-2.3% alkyl trimethyl ammonium bromide, 7-13% surfactant, 0.01-0.15% polyethylene oxide and the balance deionized water; the cleaning temperature is 60-70°C; the cleaning time is 10-180 seconds;
[0043] Preferably, in step (10), the measured poly thickness value is substituted into the model to calculate the optimal dosage of each component in the alkali solution, the cleaning temperature and the cleaning time;
[0044] Based on the optimal dosing ratio of alkali solution in actual production, the cleaning efficiency is evaluated by the change of poly thickness with cleaning time;
[0045] Based on the feedback of cleaning efficiency, the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing of the area without plating bypass are calculated under the current alkali solution formula, and the minimum cleaning time, the maximum cleaning time and the model-predicted cleaning time are sorted in ascending order, and the middle value after sorting is selected as the adjusted cleaning time;
[0046] The calculated optimal dosage of each component in the alkali solution, the cleaning temperature and the adjusted cleaning time are introduced into the cleaning process to control the execution of the cleaning process.
[0047] (11) Texturing and cleaning - Use texturing liquid (KOH: additive = 4:1~10:1, maintain the temperature at 75-85℃, and perform rapid texturing for about 4-6 minutes. The thinning amount is controlled at 0.1-0.3g; remove BSG and PSG on the back, use ammonia and hydrogen peroxide mixture, and clean at 80℃ for about 2 minutes;
[0048] (12) Double-sided aluminum oxide and silicon nitride passivation deposition - double-sided aluminum oxide deposition between 1-5nm, using PECVD to deposit SiNx or SiOx, SiNx, SiON stacked on top of each other, with a total film thickness of 70-90nm and a refractive index of 1.9-2.1;
[0049] (13) Screen printing, sintering, and testing - back electrode and gate line printing; back surface scanning using laser induced sintering to test efficiency.
[0050] Furthermore, when an N-type silicon wafer is used as a substrate, and a back contact structure uses P-poly as a P-type doping region and N-poly as an N-type doping region, the preparation process of the battery structure includes:
[0051] (1) Double-sided polishing of N-type silicon wafers; N-type silicon wafers with a resistivity of 0.5~2Ω.cm and a minority carrier lifetime >10ms are used for polishing, and the polishing depth is 3-10nm;
[0052] (2) Back-side doping with P + -poly; SiOx and poly-Si are deposited on the back side by LPCVD, where the thickness of SiOx is 1~2nm and the thickness of poly-Si is 80~300nm; B diffusion is performed on the back side, with a peak concentration of 1~9×10 19 atoms / cm 3 , square resistance is 100-500 Ω / sq;
[0053] (3) Back-side laser patterning 1 removes BSG in the N region; the back side uses green skin / green nano / purple skin / purple nano lasers to modify BSG and loosen or remove the BSG;
[0054] (4) Pickling to remove BSG on the front and edges;
[0055] (5) Use alkaline cleaning solution to remove the P on the front poly plating and the N area on the back + -poly layer: the alkali solution is prepared by mixing potassium hydroxide and a polishing additive in a mass ratio of 2-6:1, wherein the polishing additive includes 0.1-0.5% silane coupling agent, 0.8-2.3% alkyl trimethyl ammonium bromide, 7-13% surfactant, 0.01-0.15% polyethylene oxide and the balance deionized water; the cleaning temperature is 60-70°C; the cleaning time is 10-180 seconds;
[0056] (6) Back pickling to remove the tunneling oxide layer around the laser area and the tunneling oxide layer below the laser area, and further polishing;
[0057] (7) Back-side doping with N + -poly; SiOx / a-Si(n) is prepared by PECVD on the back side and then annealed, or SiOx / poly-Si is prepared by LPCVD on the back side and then phosphorus diffusion is performed. The thickness of the tunneling oxide layer is 1~2nm, the thickness of poly-Si is 40~120nm, and the peak concentration of poly-Si(n) is 2~8×10 20 atoms / cm 3 , the inflection point concentration is 7~9×10 18 atoms / cm 3 ;
[0058] (8) Back laser patterning 2 removes PSG in the P area; the back side uses green skin / green nano / purple skin / purple nano laser to modify PSG and loosen or remove PSG;
[0059] (9) Back laser patterning 3 is used to make grooves at the PN gap; specifically, green skin / green nano / purple skin / purple nano lasers are used to make laser grooves at the PN junction position;
[0060] (10) Pickling to remove PSG on the front and edges;
[0061] (11) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer: the alkali solution is prepared by mixing potassium hydroxide and a polishing additive in a mass ratio of 2-6:1, wherein the polishing additive includes 0.1-0.5% silane coupling agent, 0.8-2.3% alkyl trimethyl ammonium bromide, 7-13% surfactant, 0.01-0.15% polyethylene oxide and the balance deionized water; the cleaning temperature is 60-70°C; the cleaning time is 10-180 seconds;
[0062] (12) Back pickling to remove the tunnel oxide layer around the laser area and the tunnel oxide layer below the laser area, and then double-sided texturing;
[0063] (13) Double-sided preparation of aluminum oxide and silicon nitride passivation deposition; the thickness of aluminum oxide is 3~10nm;
[0064] (14) Screen printing, sintering, and testing: screen printing and sintering, LECO laser enhanced passivation contact performance, and finally testing and sorting.
[0065] Preferably, in step (5) and step (11), the following steps are performed respectively:
[0066] Substitute the measured poly thickness value into the model to calculate the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time;
[0067] Based on the optimal dosing ratio of alkali solution in actual production, the cleaning efficiency is evaluated by the change of poly thickness with cleaning time;
[0068] Based on the feedback of cleaning efficiency, the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing of the area without plating bypass are calculated under the current alkali solution formula, and the minimum cleaning time, the maximum cleaning time and the model-predicted cleaning time are sorted in ascending order, and the middle value after sorting is selected as the adjusted cleaning time;
[0069] The calculated optimal dosage of each component in the alkali solution, the cleaning temperature and the adjusted cleaning time are introduced into the cleaning process to control the execution of the cleaning process.
[0070] The beneficial effects of the present invention are:
[0071] The present invention realizes the effective removal of the front-surface plating of solar cells through precise alkali solution formula and cleaning condition control, and can perform real-time matching and time control based on poly thickness, and can effectively avoid cleaning time deviation caused by environmental factors or equipment fluctuations, thereby improving the conversion efficiency and stability of the battery, and is suitable for high requirements for stability and consistency in mass production.
[0072] The present invention avoids over-cleaning or under-cleaning by optimizing the cleaning time, improves the poly removal efficiency, and reduces the cleaning time and the amount of chemicals used; the optimized cleaning process reduces surface defects and polishing problems in the plating area, helps to maintain the integrity of the battery surface, thereby improving the current density and photoelectric conversion efficiency of the battery.
[0073] The present invention optimizes the cleaning process of back-contact solar cells, making the surface state of the cells more uniform and reducing surface defects, thereby improving the conversion efficiency of the cells. The solution can be optimized in real time according to the changes in the thickness of the poly layer, environmental conditions and equipment conditions in actual production to ensure the optimization of the cleaning process. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0075] Figure 1It is a flowchart of the steps of matching various parameters according to the thickness of poly in an embodiment of the present invention;
[0076] Figure 2 This is a structural diagram of a back contact solar cell with tunneling oxide passivation contact in Example 1 of the present invention;
[0077] Figure 3 This is a flow chart of the steps of a back contact solar cell with tunneling oxide passivation contact in Example 1 of the present invention;
[0078] Figure 4 A structural diagram of a back contact solar cell with tunneling oxide passivation contact in Example 2 of the present invention;
[0079] Figure 5 It is a flowchart of the steps of a back contact solar cell with tunneling oxide passivation contact in Example 2 of the present invention;
[0080] Figure 6 This is a diagram of the cleaning efficiency of N-poly in an embodiment of the present invention;
[0081] Figure 7 This is a diagram of the cleaning efficiency of P-poly in an embodiment of the present invention;
[0082] Figure numerals: 10, N-type silicon wafer substrate; 11, first tunneling oxide layer; 12, first N-poly layer; 13, P+ layer formed by boron doping; 14, first aluminum oxide layer; 15, first silicon nitride layer; 20, silicon substrate; 21, second tunneling oxide layer; 22, second N-poly layer; 23, P-poly layer; 24, second aluminum oxide layer; 25, second silicon nitride layer. DETAILED DESCRIPTION
[0083] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0084] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0085] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0086] like Figure 1~Figure 5 A method for preparing a back contact solar cell with a tunneling oxide passivation contact is shown, comprising:
[0087] N-type silicon wafer is used as substrate, and the back contact structure uses single boron diffusion or P-poly as P-type doping area and N-poly as N-type doping area;
[0088] Among them, the wrap-around plating caused by P-poly or N-poly doping on the front side is removed by alkaline cleaning;
[0089] like Figure 6 As shown, the relationship between the thickness of poly and the time of removal of poly by alkaline cleaning during the wrap-around plating produced by N-poly doping on the front side is shown in the figure. Figure 7 As shown, the relationship between the thickness of poly produced by P-poly doping on the front side and the time of removal by alkaline cleaning is shown.
[0090] The alkali solution is prepared by mixing potassium hydroxide with a polishing additive, wherein the polishing additive includes a silane coupling agent, alkyl trimethyl ammonium bromide, a surfactant, polyethylene oxide and deionized water;
[0091] Silane coupling agent can be adsorbed on the surface of borosilicate glass and phosphosilicate glass grown on silicon wafers, protecting the two silicon oxide films from alkali corrosion during the de-plating process; alkyltrimethylammonium bromide can increase the corrosion rate of the de-plating in alkaline solution, making the de-plating removal faster and more thorough; surfactants can enhance the wetting and leveling effects of the polishing liquid; polyethylene oxide can enhance the stability and effect of additives; deionized water, as a solvent, provides the necessary liquid environment so that other components can be evenly distributed and function.
[0092] The dosage of each component in the alkali solution, the cleaning temperature and the cleaning time are matched according to the thickness of the poly. The present invention conducts multiple experiments with different liquid ratios, different reaction temperatures and different reaction times to establish a model for the dosage of each component in the alkali solution, the cleaning temperature and the cleaning time, and the thickness of the poly; in actual production, for a specific poly thickness, the optimal liquid ratio and reaction temperature are found through model fitting, and the cleaning time is adjusted based on actual production, ultimately achieving the purpose of accurately removing the wrap-around plating and improving the conversion efficiency.
[0093] Preferably, the dosage of each component in the alkali solution, the cleaning temperature and the cleaning time are matched according to the thickness of the poly, including:
[0094] S1: Establish a model for the dosage of each component in the alkali solution, cleaning temperature and cleaning time, and poly thickness;
[0095] Preferably, the establishment of the model comprises the following steps:
[0096] S11: According to process requirements and experience, set reasonable parameter ranges for poly thickness, dosage of each component in alkali solution, cleaning temperature and cleaning time; wherein, poly thickness is 40~200nm, alkali solution includes potassium hydroxide and polishing additives mixed in a mass ratio of 2~6:1, polishing additives include 0.1~0.5% silane coupling agent, 0.8~2.3% alkyltrimethylammonium bromide, 7~13% surfactant, 0.01~0.15% polyethylene oxide and the balance deionized water; cleaning temperature is 60~70℃; cleaning time is 10~180sec;
[0097] S12: Conduct multiple experiments to record the effect of parameter changes on cleaning effect under different poly thicknesses, and collect current density, efficiency and surface quality data;
[0098] Specifically for poly materials of different thicknesses, multiple groups of cleaning experiments were carried out to record the cleaning effects under different alkali solution formulas, cleaning temperatures, and cleaning times. The cleaning efficiency refers to the rate of change of poly thickness during the cleaning process, and the surface quality refers to whether the surface after cleaning is uniform and flawless.
[0099] During the process, we can draw scatter plots, box plots or heat maps to preliminarily observe how factors such as poly thickness, cleaning time, and temperature affect the cleaning effect. For example, we can draw a scatter plot of poly thickness and cleaning time to observe whether the poly thickness gradually decreases with time, so as to understand the changing trend of cleaning efficiency. By analyzing the distribution characteristics of the data, we can check whether there are outliers (such as experimental data with poor cleaning effects) and evaluate the influence of various parameters (such as temperature and alkali solution formula ratio) on the cleaning results.
[0100] S13: Analyze the experimental data using statistical analysis software and identify the best parameter combination as the basis for the model;
[0101] Specifically, by establishing a multiple regression model, the cleaning efficiency or surface quality (such as smoothness and uniformity after cleaning) is used as the dependent variable, and the poly thickness, alkali solution component ratio, temperature and cleaning time are used as independent variables. Through regression analysis, the contribution of each independent variable to the cleaning effect can be obtained. According to the significance level of the coefficient (judged by the p value), the parameters with significant effects on the cleaning effect are screened out. In order to further confirm the influence of each factor, a single or multi-factor variance analysis can be performed to determine the significant differences in the cleaning effect of different poly thicknesses, alkali solution ratios, cleaning temperatures, cleaning times, etc. Based on the response surface constructed by the regression model, the combination of each parameter can be further optimized to find the best combination of conditions.
[0102] On this basis, through regression analysis and response surface optimization, the optimal combination of alkali ratio, cleaning temperature and time under different poly thickness conditions is identified. Through multiple verification experiments, it is confirmed whether these parameter combinations can stably achieve efficient cleaning. If the verification effect is good, these parameters will be used as the basic input parameters of the model.
[0103] S2: Based on the established model, the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time are calculated in real time for the poly thickness actually measured in each preparation;
[0104] S21: During each production process, the poly thickness value measured in real time is used as input and input into the model;
[0105] S22: The model calculates the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time in real time according to the current poly thickness value, which is used to control the execution of the cleaning process;
[0106] S3: Based on the optimal dosing ratio of alkali solution in actual production, the change of poly thickness with cleaning time is used to evaluate the cleaning efficiency; the change of poly thickness is detected by implementing a data acquisition system, and the system's acquisition frequency is once per second;
[0107] S4: Based on the cleaning efficiency feedback, calculate the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing in the area without de-plating under the current alkali solution formula, and compare them with the cleaning time predicted by the model;
[0108] S5: sort the minimum cleaning time, the maximum cleaning time and the cleaning time predicted by the model in ascending order, and select the middle value after sorting as the adjusted cleaning time;
[0109] By sorting and selecting the middle value of the minimum, maximum and model predicted time as the cleaning time, excessive or insufficient cleaning can be avoided to the greatest extent, ensuring that poly is completely removed within the safest time. After sorting, the middle value is selected as the optimization strategy for the cleaning time, which improves the fault tolerance of the system, can adapt to small fluctuations in the cleaning time within a certain range, and improves the stability of the cleaning process. The adjusted cleaning time is calculated based on real-time data, which meets safety requirements and is reliable. It provides an optimized data basis for subsequent model updates.
[0110] S6: The adjusted cleaning time, the alkali solution with the optimal dosage ratio calculated, and the cleaning temperature are used as process parameters to clean and remove the poly.
[0111] On this basis, the present invention uses the adjusted cleaning time, the calculated optimal dosage ratio of alkali solution, the cleaning temperature, and the measured poly thickness as a data set, and adds it to the model training set, so that the model can continuously optimize itself according to the latest data, thereby improving the cleaning accuracy and efficiency. After each adjustment, the model will update the cleaning time based on the latest production data, so that the model gradually fits the actual working conditions and continuously optimizes the production process.
[0112] Example 1
[0113] like Figure 2 and Figure 3 As shown, this embodiment uses an N-type silicon wafer with a resistivity of 1~3Ω.cm and a minority carrier lifetime>10ms. A back-contact solar cell with a tunneling oxide passivation contact is prepared, which includes an N-type silicon wafer substrate 10, the front side of which is provided with a first aluminum oxide layer 14 and a first silicon nitride layer 15 in sequence from the inside to the outside; the back side of the N-type silicon wafer substrate 10 is provided with an N region and a P region and a PN gap, wherein the N region is provided with a first tunneling oxide layer 11, a first N-poly layer 12, a first aluminum oxide layer 14 and a first silicon nitride layer 15 in sequence from the inside to the outside; the P region is provided with a P+ layer 13 formed by boron doping, a first aluminum oxide layer 14 and a first silicon nitride layer 15 in sequence from the inside to the outside; the PN gap is provided with a first aluminum oxide layer 14 and a first silicon nitride layer 15 in sequence from the inside to the outside;
[0114] A method for preparing a back contact solar cell with a tunneling oxide passivation contact comprises the following steps:
[0115] (1) Double-sided polishing of N-type silicon wafers: First polishing is performed in a slot machine with a polishing thickness of about 7 μm;
[0116] (2) Back side boron diffusion - Boron doping is performed in a high temperature furnace tube, and the temperature is 850~1100℃ for doping advancement and oxidation. The BSG thickness is controlled at 100nm and the doping square resistance is controlled at 350ohm / sq.
[0117] (3) Back laser patterning 1 to remove BSG in the N region - using a green laser with a power of 10W in a single scan to remove BSG in the back N region;
[0118] (4) Pickling to remove the front and edge BSG - Use a chain cleaning machine with an HF concentration of 40% by volume to remove the BSG layer on the front and side;
[0119] (5) Perform alkaline polishing on the back laser patterning 1 area, front side and edge - polishing using a tank cleaning machine, using an alkaline cleaning solution - potassium hydroxide: polishing additive = 3:1, the temperature is controlled at 80 ° C, and the polishing weight loss is about 0.15g;
[0120] (6) Back-side doping with N + -poly——Both PECVD and LPCVD methods can be used for doping; the thickness of doped poly is controlled at 100nm, the thickness of PSG is controlled at 50nm, and the doped square resistance is controlled at 50ohm / sq;
[0121] (7) Back laser patterning 2 to remove PSG in the P region - using a green laser with a power of 10W in a single scan to remove PSG in the back P region;
[0122] (8) Back laser patterning 3 to remove the oxide layer BSG / PSG at the PN gap - using a green laser with a power of 15W for a single scan to remove the oxide layer BSG / PSG at the back PN gap;
[0123] (9) Pickling to remove PSG on the front and edges: Use a chain cleaning machine with an HF concentration of 15% by volume to remove the PSG layer on the front and sides;
[0124] (10) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer——the alkaline solution is prepared by mixing potassium hydroxide and a polishing additive in a mass ratio of 4:1, the polishing additive includes 0.3% silane coupling agent, 1.6% alkyltrimethylammonium bromide, 10% surfactant, 0.08% polyethylene oxide, and the balance is deionized water; the cleaning temperature is 65°C; the cleaning time is 50 seconds.
[0125] (11) Texturing and cleaning - Use texturing liquid (KOH: additive = 6:1, maintain the temperature at 80°C, and perform rapid texturing for about 5 minutes. The thinning amount is controlled at about 0.20g; remove the BSG and PSG on the back, use a mixture of ammonia and hydrogen peroxide, and clean at 80°C for about 2 minutes;
[0126] (12) Double-sided aluminum oxide and silicon nitride passivation deposition - 3nm of aluminum oxide is deposited on both sides, and SiNx or a multilayer film of SiOx, SiNx, and SiON is deposited in sequence using PECVD, with a total film thickness of 80nm and a refractive index of 2.0;
[0127] (13) Screen printing, sintering, and testing - back electrode and gate line printing; back surface scanning using laser induced sintering to test efficiency.
[0128] Example 2
[0129] like Figure 4 and Figure 5 As shown, this embodiment uses an N-type silicon wafer with a resistivity of 0.5~2Ω.cm and a minority carrier lifetime>10ms. A back-contact solar cell with a tunneling oxide passivation contact is prepared, which includes an N-type silicon substrate 20, the front side of which is provided with a second aluminum oxide layer 24 and a second silicon nitride layer 25 in sequence from the inside to the outside; the back side of the silicon substrate 20 is provided with an N region and a P region and a PN gap, wherein the N region is provided with a second tunneling oxide layer 21, a second N-poly layer 22, a second aluminum oxide layer 24 and a second silicon nitride layer 25 in sequence from the inside to the outside; the P region is provided with a second tunneling oxide layer 21, a P-poly layer 23, a second aluminum oxide layer 24 and a second silicon nitride layer 25 in sequence from the inside to the outside; the PN gap is provided with a second aluminum oxide layer 24 and a second silicon nitride layer 25 in sequence from the inside to the outside;
[0130] A method for preparing a back contact solar cell with a tunneling oxide passivation contact comprises the following steps:
[0131] (1) Double-sided polishing of N-type silicon wafer: polishing depth is 5nm;
[0132] (2) Back-side doping with P + -poly: SiOx and poly-Si are deposited on the back side by LPCVD, where the thickness of SiOx is 1.4 nm and the thickness of poly-Si is 190 nm; the back side is B diffused, with a peak concentration of 5×10 19 atoms / cm 3 , square resistance is 350Ω / sq;
[0133] (3) Back laser patterning 1 to remove BSG in the N region: Green laser is used to modify BSG on the back side to loosen or remove the BSG;
[0134] (4) Pickling to remove BSG on the front and edges:
[0135] (5) Use alkaline cleaning solution to remove the P on the front poly plating and the N area on the back + -poly layer;
[0136] The specific process is: the alkaline solution includes potassium hydroxide and a polishing additive mixed in a mass ratio of 6:1, the polishing additive includes 0.4% silane coupling agent, 1.8% alkyltrimethylammonium bromide, 11% surfactant, 0.10% polyethylene oxide, and the balance is deionized water; the cleaning temperature is 70°C; the cleaning time is 50 seconds.
[0137] (6) The back side is pickled to remove the tunnel oxide layer around the tunnel oxide layer and the tunnel oxide layer under the laser area, and further polished; 2% hydrofluoric acid is used for cleaning for 30 seconds; polishing is carried out at 65 ° C with an aqueous solution of 2.3% KOH and 1.3% BP65V34 additive for 200 seconds, and finally RCA cleaning is performed.
[0138] (7) Back-side doping with N + -poly: SiOx / a-Si(n) is prepared by PECVD on the back side, followed by annealing;
[0139] (8) Back laser patterning 2 to remove PSG in the P area: The back side is modified by green laser to loosen or remove the PSG;
[0140] (9) The back side is grooved at the PN gap using green laser patterning 3;
[0141] (10) Pickling to remove PSG on the front and edges;
[0142] (11) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer;
[0143] The specific process is: the alkaline solution is prepared by mixing potassium hydroxide and a polishing additive in a mass ratio of 6:1, the polishing additive includes 0.4% silane coupling agent, 2.0% alkyltrimethylammonium bromide, 12% surfactant, 0.10% polyethylene oxide, and the balance is deionized water; the cleaning temperature is 68°C; the cleaning time is 30 seconds.
[0144] (12) Back pickling to remove the tunnel oxide layer around the laser area and the tunnel oxide layer below the laser area, and then double-sided texturing;
[0145] (13) Double-sided preparation of aluminum oxide and silicon nitride passivation deposition: the thickness of aluminum oxide is 5 nm;
[0146] (14) Screen printing, sintering, and testing: LECO laser enhances the passivation contact performance, and finally conducts testing and sorting.
[0147] Comparative Example 1
[0148] Preparation of conventional TOPCon cells;
[0149] N-type silicon wafers with a resistivity of 1.0 Ω.cm and a minority carrier lifetime of >10ms are used for texturing to remove damage and form a pyramid structure for surface light trapping;
[0150] The front B diffuses to form a PN junction, the B diffusion junction depth is 0.7μm, and the peak concentration is 1.42×10 19 atoms / cm 3 , square resistance is 125Ω / sq;
[0151] The back side is cleaned with HF to remove the BSG on the back side and around, and the back side is polished with alkali to remove the B wrapping, and the tower base size is 11μm;
[0152] The tunneling oxide passivation structure was prepared by back PECVD method, where the thickness of the tunneling oxide layer was 1.5 nm and the a-Si(n + ) thickness is 80nm;
[0153] Annealing to form poly-Si(n + ) has a peak concentration of 3×10 20 atoms / cm 3 , the inflection point concentration is 8-9×10 18 atoms / cm 3 ;
[0154] Front HF cleaning to remove PSG and de-wrap plating;
[0155] The front side is passivated with aluminum oxide, and the thickness of aluminum oxide is 3nm;
[0156] Front / back silicon nitride passivation;
[0157] The main / sub-gate lines are formed by screen printing on the front / back sides, ohmic contacts are formed by sintering, light injection improves passivation and light decay, and LECO laser enhances passivation contact performance.
[0158] Comparative Example 2
[0159] Compared with Example 1, except for step (10), the remaining steps of this comparative example are exactly the same and will not be repeated here.
[0160] Specific steps (10) Use alkaline cleaning solution to remove the N +-poly layer——Use conventional polishing additives for de-plating and cleaning, potassium hydroxide (KOH): polishing additive = 3:1, the temperature is maintained at 80℃, and the time is about 300sec; the wt.% ratio of alkyltrimethylammonium bromide and surfactant in conventional additives is relatively low, and it requires a higher reaction temperature and a long polishing cleaning time to remove the plating. At the same time, high temperature and long time will damage the suede surface of the non-plating area, resulting in obvious color difference after coating and poor passivation effect; the structure is not removed cleanly, resulting in serious leakage.
[0161] Performance Testing
[0162] Taking the performance of the conventional TOPCon battery prepared in Comparative Example 1 as a benchmark, the battery structures obtained in Examples 1-2 and Comparative Example 2 were tested. The test results are shown in Table 1.
[0163] Table 1
[0164]
[0165] It can be seen that the present invention utilizes alkaline washing solution to remove the wrap-around plating caused by poly doping on the front side through precise control, and during the process ensures that the velvet / polished surface of the non-wrapped plating area of the front side is not affected, thereby avoiding a reduction in battery efficiency.
[0166] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a back contact solar cell with a tunneling oxide passivation contact, characterized in that: include: N-type silicon wafer is used as substrate, and the back contact structure uses single boron diffusion or P-poly as P-type doping area and N-poly as N-type doping area; Among them, the wrap-around plating caused by P-poly or N-poly doping on the front side is removed by alkaline cleaning; The alkali solution is prepared by mixing potassium hydroxide with a polishing additive, wherein the polishing additive includes a silane coupling agent, alkyl trimethyl ammonium bromide, a surfactant, polyethylene oxide and deionized water; The dosage of each component in the alkali solution, the cleaning temperature and the cleaning time are matched according to the thickness of the poly, including: Establish models for the dosage of each component in the alkali solution, cleaning temperature and cleaning time, and poly thickness; calculate the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time in real time based on the model for the poly thickness measured in each preparation; evaluate the cleaning efficiency based on the change of poly thickness with cleaning time in production of the alkali solution with the optimal dosage ratio; calculate the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing in the non-wrap-plating area under the current alkali solution formula based on the cleaning efficiency, and sort the cleaning times predicted by the model in ascending order, and select the middle value after sorting as the adjusted cleaning time; use the optimal dosage ratio and cleaning temperature as process parameters to clean and remove poly.
2. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 1, characterized in that: The change of poly thickness is detected by implementing a data acquisition system, and the system's acquisition frequency is once per second.
3. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 1, characterized in that: The establishment of the model includes the following steps: Set the parameter ranges for poly thickness, dosage of each component in the alkali solution, cleaning temperature and cleaning time; Conduct multiple sets of experiments to record the effect of parameter changes on cleaning results at different poly thicknesses, and collect current density, efficiency, and surface quality data; Analyze experimental data using statistical analysis software to identify the best parameter combinations as the basis for the model; During each production process, the poly thickness value measured in real time is used as input into the model; According to the current poly thickness value, the model calculates the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time in real time to control the execution of the cleaning process.
4. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 3, characterized in that: The parameter range is set as: The poly thickness is 40~200nm, the alkali solution includes potassium hydroxide and a polishing additive mixed in a mass ratio of 2~6:1, the polishing additive includes 0.1~0.5% silane coupling agent, 0.8~2.3% alkyltrimethylammonium bromide, 7~13% surfactant, 0.01~0.15% polyethylene oxide and the remainder deionized water; the cleaning temperature is 60~70℃; the cleaning time is 10~180sec.
5. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 1, characterized in that: When an N-type silicon wafer is used as a substrate, a back contact structure uses a single boron diffusion as a P-type doping region, and N-poly is used as an N-type doping region, the preparation process of the battery structure includes: (1) Double-sided polishing of N-type silicon wafers; (2) Back side boron diffusion; (3) Back-side laser patterning 1 to remove BSG in the N region; (4) Pickling to remove BSG on the front and edges; (5) Alkali polishing of the laser patterned area 1 on the back, the front and the edge; (6) Back-side doping with N + -poly; (7) Back laser patterning 2 to remove PSG in the P region; (8) Back-side laser patterning 3 removes the oxide layer BSG / PSG at the PN gap; (9) Pickling to remove PSG on the front and edges; (10) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer; (11) Velvet cleaning; (12) Double-sided aluminum oxide and silicon nitride passivation deposition; (13) Screen printing, sintering and testing.
6. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 5, characterized in that: In step (10), the measured poly thickness value is substituted into the model to calculate the optimal dosage of each component in the alkali solution, the cleaning temperature and the cleaning time; Based on the optimal dosing ratio of alkali solution in actual production, the cleaning efficiency is evaluated by the change of poly thickness with cleaning time; Based on the feedback of cleaning efficiency, the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing of the area without de-plating are calculated under the current alkali solution formula, and the minimum cleaning time, the maximum cleaning time and the model-predicted cleaning time are sorted in ascending order, and the middle value after sorting is selected as the adjusted cleaning time; The calculated optimal dosage of each component in the alkali solution, the cleaning temperature and the adjusted cleaning time are used in the cleaning process to control the execution of the cleaning process.
7. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 1, characterized in that: When an N-type silicon wafer is used as a substrate, and a back contact structure uses P-poly as a P-type doping region and N-poly as an N-type doping region, the preparation process of the battery structure includes: (1) Double-sided polishing of N-type silicon wafers; (2) Back-side doping with P + -poly; (3) Back-side laser patterning 1 to remove BSG in the N region; (4) Pickling to remove BSG on the front and edges; (5) Use alkaline cleaning solution to remove the P on the front poly plating and the N area on the back + -poly layer; (6) Back pickling to remove the tunneling oxide layer around the laser area and the tunneling oxide layer below the laser area, and further polishing; (7) Back-side doping with N + -poly; (8) Backside laser patterning 2 to remove PSG in the P region; (9) Back laser patterning 3 to create grooves at the PN gap; (10) Pickling to remove PSG on the front and edges; (11) Use alkaline cleaning solution to remove the N on the front poly plating and the back P area + -poly layer; (12) Back pickling to remove the tunnel oxide layer around the laser area and the tunnel oxide layer below the laser area, and then double-sided texturing; (13) Double-sided preparation of aluminum oxide and silicon nitride passivation deposition; (14) Screen printing, sintering and testing.
8. The method for preparing a back contact solar cell with a tunneling oxide passivation contact according to claim 7, characterized in that: In step (5) and step (11), perform the following steps respectively: Substitute the measured poly thickness value into the model to calculate the optimal dosage of each component in the alkali solution, cleaning temperature and cleaning time; Based on the optimal dosing ratio of alkali solution in actual production, the cleaning efficiency is evaluated by the change of poly thickness with cleaning time; Based on the feedback of cleaning efficiency, the minimum cleaning time required for complete removal of poly and the maximum cleaning time required for polishing of the area without de-plating are calculated under the current alkali solution formula, and the minimum cleaning time, the maximum cleaning time and the model-predicted cleaning time are sorted in ascending order, and the middle value after sorting is selected as the adjusted cleaning time; The calculated optimal dosage of each component in the alkali solution, the cleaning temperature and the adjusted cleaning time are used in the cleaning process to control the execution of the cleaning process.
Citation Information
Patent Citations
Winding plating removing method of solar cell and application of winding plating removing method
CN117476814A